Cambios necesarios en una sociedad global - Rodríguez Camacho, Álvaro (Nómadas. Critical Journal of Social and Juridical Science, 2008)
We often wonder about the possibility of changes in our global society. From the point of view of Political Philosophy, we reflect on the premises and challenges which are necessary for that transformation. And we do it by taking into account three levels of concretion: international, national and regional.
Keywords: Human Rights; Social welfare; Political transformation; Social agreement; Fourth pillar; Social inclusion; International solidarity; The Mediterranean Treaty